Intellectual Capital : A System Thinking Analysis in Revamping the Exchanging Information in University-Industry Research Collaboration - Abeda, Muhammad Iqbal; Narayanan, Kulathuramaiyer; Adnan Shahid, Khan; Johari, Abdullah; Mussadiq Ali, Khan (MDPI, 2022)
University-industry research collaboration (UIRC) is a major source for research, innovations and sustainable economic growth. Despite the extensive evidence on the importance of such collaboration in developed and developing countries, literature related to the strengthening of this collaboration, along with its innovation performance, is still scarce. Scholars believe that the impact of exchanging information has a vigorous influence on researcher’s innovative activities as well as research and innovations. Moreover, to flatten the flow of exchanging information between researchers, it is mandatory to refurbish human capital in conjunction with intellectual capital, along with their reinforcing factors i.e., communication and networking, respectively. In this paper, we evaluate the influence of human capital and intellectual capital along with their corresponding reinforcing factors on exchanging information using the system thinking method. Evidence from UIRC in Malaysia provides empirical corroboration that intellectual capital along with its reinforcing factors has a significant influence on exchanging information. Thus, the findings of this research suggest that intensifying the capabilities of intellectual capital with a reinforcing effect can sustain the circulation of exchanging information.